ANALYSIS OF INFLUENCE OF LEADERSHIP AND MOTIVATION TO WORK ON THE PERFORMANCE OF EMPLOYEES PT. TRADING COMPANY INDONESIA (Persero) CAB. LAMPUNG - Tri Nanda Ganeli; Andri Winata (Proceeding International Conference on Information Technology and Business, 2018)
The current conditions in PT. Trading Company Indonesia (Persero) Cab. Lampung, where the employee's performance is still not optimal due to the leadership of the lack of attention to its employees and the low mativasi employee. This study aimed to determine the effect of leadership on employee performance, the effect of work motivation on employee performance, leadership and motivation influence on employee performance PT. Trading Company Indonesia (Persero) Cab. Lampung,This type of research used in this research is quantitative research. Data collection techniques used were interviews, questionnaires, observations. The population in this study are employees PT. Trading Company Indonesia (Persero) Cab. Lampung which amounts to 102 employees. The sampling technique in this study using a systematic sampling technique with a sample size that is 51 respondents. Analysis of data using multiple linear regression t test and F .The results of the analysis produces a value of determination coefficient R = 0.872 and R Square .760, In the t-test probability variables Leadership produce sig 0.000 0.005 or 9.671 t t table 1.676, t-test probability variables Work Motivation produce sig 0.000 0.005 or 11,583 t t table 1.676. This study therefore shows that there is no significant influence on Employee Performance Leadership, Motivation Work on the Performance of Employees. While the F test obtained Fhitung76.137 Ftabel 3.19 or sig 0.000 0.05. Then the results of the study indicate that there is no significant influence on the Labor Leadership and Motivation Employee Performance PT. Trading Company Indonesia (Persero) Cab. Lampung.Keywords: Leadership, Work Motivation and Performance